Caracterização de bactérias láticas da microbiota de grãos de Kefir cultivados em leite ou água com açúcar mascavo por metodologias dependentes e independentes de cultivos - Débora Ferreira Zanirati (2012)
The Kefir grains are similar in structure to pieces of cauliflower, composed by a variety of bacteria and yeast which are firmly bonded and encapsulated by an insoluble polysaccharide matrix,, that are used to produce a sour, slightly alcoholic fermented beverage, called Kefir. Although Kefir grains were originally cultured in milk, other substrates have been used as culture medium (aqueous solution of brown sugar or soy milk). Thus, the aim of this study was to identify and characterize the lactic acid bacteria of kefir grains, using culture-dependent and culture- independent methods. For this purpose, eight samples of kefir grains were obtained from Viçosa (MG), Belo Horizonte (MG), Salvador (BA), Curitiba (PR) and Divinópolis (MG), four grown in water with brown sugarand four in milk. Ten grams of each sample were diluted and plated on modified MRS agarand M-17 agar. After preliminary identification tests, 117 isolates suggestive of Lactobacillus were submitted to identification by PCR- ARDRA and the species identified were: L. crispatus, L. casei, L. kefiri, L. diolivorans, L. perolens, L. mali, L. satsumensis and L. parafarraginis. Leuconostoc mesenteroides, Oenococcus oeni and Lactococcus lactis were also isolated and identified by the culture-dependent method. Ten grams of four samples of Kefir grains were treated to obtain total DNA, being submitted to PCR and 16SrRNA gene amplicons obtained were cloned and transformed. Eighty colonies were randomly selected and analyzed by colony PCR using specific primers of the TOPO 2.1 vector. The amplicons of fifty transformant colonies were separately digested with restriction enzymes TaqI and Sau 3AI, for grouping of the samples and subsequent sequencing. Through this culture-independent method, species were identified as follows: L. kefiranofaciens, L. kefiri, L. satsumensis, L. hilgardii, L. mali, L. paracasei, L. nagelii, L. casei, Oenococcus kitaharae, Oenococcus oeni, Enterobacter ludwigii and Klebsiella pneumoniae, and two non-cultivable microorganisms were also identified: uncultured bacterium clone-y OTU2 and uncultured Lactobacillus. Some species of lactobacilli were not recovered by culture-dependente methodbut were detected by culture-independent method. One the other hand, some lactobacilli were cultivated but not detected by cultureindependentmethod. These results suggest that bothculture-independent and culturedependent methods areimportant to understand the diversity of lactic acid bacteria in Kefir grains. Besides, food matrix and origin place might interfere with lactic acid bacteria diversityof Kefir grains.